Protein Kinase CK2 represents a new target to boost Ibrutinib and Venetoclax induced cytotoxicity in mantle cell lymphoma - Manni, Sabrina; Pesavento, Maria; Spinello, Zaira; Saggin, Lara; Arjomand, Arash; Fregnani, Anna; Quotti Tubi, Laura; Scapinello, Greta; Gurrieri, Carmela; Semenzato, Gianpietro; Trentin, Livio; Piazza, Francesco (Frontiers in Cell and Developmental Biology, 2022)
Mantle cell lymphoma (MCL) is an incurable B cell non-Hodgkin lymphoma, characterized by frequent relapses. In the last decade, the pro-survival pathways related to BCR signaling and Bcl-2 have been considered rational therapeutic targets in B cell derived lymphomas. The BTK inhibitor Ibrutinib and the Bcl-2 inhibitor Venetoclax are emerging as effective drugs for MCL. However, primary and acquired resistance also to these agents may occur. Protein Kinase CK2 is a S/T kinase overexpressed in many solid and blood-derived tumours. CK2 promotes cancer cell growth and clonal expansion, sustaining pivotal survival signaling cascades, such as the ones dependent on AKT, NF-κB, STAT3 and others, counteracting apoptosis through a “non-oncogene” addiction mechanism. We previously showed that CK2 is overexpressed in MCL and regulates the levels of activating phosphorylation on S529 of the NF-κB family member p65/RelA. In the present study, we investigated the effects of CK2 inactivation on MCL cell proliferation, survival and apoptosis and this kinase’s involvement in the BCR and Bcl-2 related signaling. By employing CK2 loss of function MCL cell models, we demonstrated that CK2 sustains BCR signaling (such as BTK, NF-κB and AKT) and the Bcl-2-related Mcl-1 expression. CK2 inactivation enhanced Ibrutinib and Venetoclax-induced cytotoxicity. The demonstration of a CK2-dependent upregulation of pathways that may antagonize the effect of these drugs may offer a novel strategy to overcome primary and secondary resistance.